Characterization of influenza A(H1N1)pdm09 viruses isolated from Nepalese and Indian outbreak patients in early 2015. Issue 5 (9th August 2017) - Nakamura, Kazuya; Shirakura, Masayuki; Fujisaki, Seiichiro; Kishida, Noriko; Burke, David F.; Smith, Derek J.; Kuwahara, Tomoko; Takashita, Emi; Takayama, Ikuyo; Nakauchi, Mina; Chadha, Mandeep; Potdar, Varsha; et al.
Abstract : We characterized influenza A(H1N1)pdm09 isolates from large‐scale outbreaks that occurred in Nepal and India in early 2015. Although no specific viral features, which may have caused the outbreaks, were identified, an S84N substitution in hemagglutinin was frequently observed. Chronological phylogenetic analysis revealed that these Nepalese and Indian viruses possessing the S84N substitution constitute potential ancestors of the novel genetic subclade 6B.1 virus that spread globally in the following (2015/16) influenza season. Thus, active surveillance of circulating influenza viruses in the Southern Asia region, including Nepal and India, would be beneficial for detecting novel variant viruses prior to their worldwide spread.